2019
DOI: 10.1002/ddr.21509
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin reduces inflammation in knee osteoarthritis rats through blocking TLR4 /MyD88/NF‐κB signal pathway

Abstract: Preclinical Research & Development Curcumin has been shown to possess a series of beneficial effects, such as antiinflammatory, antioxidant, analgesic, and promoting healing. However, the effect and relative mechanism of curcumin on knee osteoarthritis (OA) have not been elucidated. The aim of this study is to explore the protective effect of curcumin on monosodium iodoacetate (MIA)‐induced OA. Forty‐eight rats were randomized into four experimental groups: control group, OA group, OA + PBS group, and OA + c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
71
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(80 citation statements)
references
References 33 publications
9
71
0
Order By: Relevance
“…Ding et al found that miR-93 inhibited chondrocyte apoptosis and inflammation in OA by targeting the TLR4/NF-jB signaling pathway [25]. Zhang et al suggested that curcumin reduced inflammation in knee OA rats through blocking [26]. In the present study, we found that TLR4 acted as a target of miR-27a-3p.…”
Section: Discussionsupporting
confidence: 61%
“…Ding et al found that miR-93 inhibited chondrocyte apoptosis and inflammation in OA by targeting the TLR4/NF-jB signaling pathway [25]. Zhang et al suggested that curcumin reduced inflammation in knee OA rats through blocking [26]. In the present study, we found that TLR4 acted as a target of miR-27a-3p.…”
Section: Discussionsupporting
confidence: 61%
“…Its wide spectrum of biological activities including antiviral [5], antioxidant [6], neuroprotective [7], antidepressant [8], and anti-inflammatory effects [9]. In addition, curcumin has shown an anti-nociceptive effect in different types of pain, such as inflammatory pain [4,7,10], visceral pain [11], musculoskeletal pain [12], burning pain [13], and neuropathic pain [14][15][16][17]. Curcumin may alleviate neuropathic pain through inhibiting the expression of CX3CR1 by the activation of NF-κβ p65 in the dorsal horn of the spinal cord and dorsal root ganglion (DRG) [16].…”
mentioning
confidence: 99%
“…When inflammatory factors increase, the secretion of vasoactive diastolic factors such as NO and prostacyclin decreases and the vasoconstrictor factor thromboxane A2 increases, leading to the occurrence of preeclampsia (Perucci, Corrêa, and Dusse ()). Related studies have shown that activation of the MyD88/NF‐κB signaling pathway contributes to inflammatory response (Wang, Dong, & Wang, ; Zhang & Zeng, ) and cell apoptosis (Li et al, ; Zheng, Shen, & Ye, ). The results of the present study showed that preeclampsia‐induced apoptosis of placental cells was effectively inhibited after Gas treatment, and the underlying mechanism may involve downregulated activity of MyD88/NF‐κB signaling pathway.…”
Section: Discussionmentioning
confidence: 99%